Genetic variation in isolated populations of Drosophila mercatorum (Diptera: Drosophilidae) in semi-arid ecosystems - ESTRADA-F., ANA PATRICIA; PRIETO-S., RODRIGO (Revista Colombiana de Entomología, 2011)
Variations in external and internal genitalia could constitute into pre-zygote barriers that prevent mating, contributing to the divergence between populations of species and allowing the emergence of new species. Sexual characteristics like mating, were taken into account to study the evolutionary processes involved in the morphology differentiation of the genitalia, for this purpose, there were conducted interpopulation crossings and morphometric analysis of external and internal genitalia of two populations of Drosophila mercatorum and its respective hybrids, collected in the Tatacoa Desert (Huila) and the Patía valley (Nariño), considering that these are important taxonomic characters, even to the level of subspecies and races. Morphometric analysis of non-sexual related characteristic such as wings and abdominal stains were performed to compare the variability between populations, as well as to obtain their correlations, by using 28 individuals per population for geometric morphometrics and 20 for the traditional one, as in the case of the aedeagus. Less variability in these structures and a positive correlation for the wing size and the aedeagus were found. The number of sows in the clasp, the shape of the wing and abdominal stains did not show significant differences between populations; however, the decrease in the offspring produced through the inter-population crossings and back-crossings, and the morphological variation in the aedeagus, allow differentiating them as geographic races.